BMC Systems Biology
BMC Systems Biology is an open access journal publishing original peer-reviewed research articles in experimental and theoretical aspects of the function of biological systems at the molecular, cellular or organismal level, in particular those addressing the engineering of biological systems, network modelling, quantitative analyses, integration of different levels of information and synthetic biology.